The Model of the Spirituality of Upbringing in the Dimension of Modern Paradigmatic Shifts - Rastrygina, Alla; Koloskova, Zhanna; Nazarenko, Maryna (Journal of History Culture and Art Research, 2019)
The article presents the authors’ position on the possibilities of using the concept of the spirituality of upbringing as a model that can become an effective basis in creating the latest paradigm of education. This makes it possible to solve the cultural-educational and socio-pedagogical problems that exist in modern higher education and are actualized in the era of globalization. It helps to return to higher education its status of the center of the forming of the spirituality of people on the principles of cultural-creative self-development and self-realization. The article also reveals conceptual foundations of the considered model, which are presented as vectors that stipulate the introduction of the phenomenon of the spirituality of upbringing into the educational practice of both, the higher education and education in general, by the subjects of the educational process. Particular attention is given on the outlining and substantiating of a fragment of the modern educational reality - the spirituality of upbringing as a phenomenon that is being transformed by the subjects of the upbringing process here and now, and reflects the becoming and maturity of each participant of this process and his role as a subject of the social environment. It determines and systematizes the development of the modern democratic culture of society. The introduction of the concept of spirituality of upbringing into the modern educational space as a model of the newest paradigm of education enables practical implementation of the phenomenon of the spirituality of upbringing - the inspiring of the environment, which is being transformed by the subjects.